Analisis Strategi Daya Saing Bisnis di Era Digital - Maha Puspa Ardhana; Munawaroh Munawaroh (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This research aims to explore the strategies implemented by companies to increase competitiveness in the digital era. Using a qualitative approach with a technology case study in Indonesia, namely the company PT Bukalapak.com. This research found that digital transformation, product innovation, customer experience expertise, and cross-sector collaboration are key strategies that support business competitiveness. This study concludes that companies need to integrate technology with organizational values ​​to remain relevant in a dynamic business environment.